Pairs trading : strategy refinements - Ribeiro, Ricardo Jorge Madureira (2016)
In this paper, we apply the pairs trading strategy, original presented by Nunzio Tartaglia in mid-80´s, for the period between 2004 and 2014, to stocks listed in the London Stock Exchange. Our trading strategy seems to be highly profitable, with an average 6-month excess return of 15.39%. The strategy also proved to have better results when faced trouble economic environments like the subprime crisis. We have implemented several add-ons to the strategy, aiming to reduce its risk. A new liquidity restriction was implemented in selecting pairs so that the strategy is not constrained by any concerns about liquidity problems. Another implementation was the creation of stop loss strategies based on number of days with losses and by loss percentage, which, however, proved to be unrewarding on the attempt to maximize the returns. On the other hand, by proving the unfeasibility of the stop loss strategies, we also proved the robustness of our strategy because we perceive that even if the return of the pair is going down for consecutive days or for a certain percentage, it ends up converging.